Critical caring theory and public health nursing advocacy for comprehensive sexual health education. Issue 1 (4th December 2017) - Dickson, Elizabeth; Lobo, Marie L.
Abstract: Public health nurses (PHNs) often work with adolescent populations at risk for unplanned pregnancies who do not have access to comprehensive sexual health education (CSHE). Evidence‐based CSHE can have a significant protective effect on adolescent sexual behaviors. This article applies critical caring theory to public health nursing advocacy for CSHE. Critical caring theory defines the social justice work of PHNs as an expression of their caring as nurses. The lack of CSHE in schools for adolescents is a social justice issue, and PHNs can be important advocates. The purpose of this article is to explore how critical caring theory can inform public health nursing practice regarding the importance of CSHE advocacy with the goal of creating equitable access to CSHE for all adolescents.